Emphasizing the Role of Long Non-Coding RNAs (lncRNA), Circular RNA (circRNA), and Micropeptides (miPs) in Plant Biotic Stress Tolerance - Anirban Bhar; Amit Roy (Plants, 2023)
Biotic stress tolerance in plants is complex as it relies solely on specific innate immune responses from different plant species combating diverse pathogens. Each component of the plant immune system is crucial to comprehend the molecular basis underlying sustainable resistance response. Among many other regulatory components, long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) have recently emerged as novel regulatory control switches in plant development and stress biology. Besides, miPs, the small peptides (100–150 amino acids long) encoded by some of the non-coding portions of the genome also turned out to be paramount regulators of plant stress. Although some studies have been performed in deciphering the role of miPs in abiotic stress tolerance, their function in regulating biotic stress tolerance is still largely elusive. Hence, the present review focuses on the roles of long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) in combating biotic stress in plants. The probable role of miPs in plant–microbe interaction is also comprehensively highlighted. This review enhances our current understanding of plant lncRNAs, circRNAs, and miPs in biotic stress tolerance and raises intriguing questions worth following up.